Analisis Implementasi Keberhasilan Sistem Informasi Manajemen Puskesmas (SIMPUS): Tinjauan Teoritis - I Wayan Santika; Dety Mulyanti (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
Puskesmas Management Information System (PMIS) as a modern technology that is very important in data processing procedures based on information technology and integrated with manual procedures and other procedures to produce timely and effective information to support management decision-making processes. The PMIS application is a form of innovation in the public sector that focuses on the health sector which can accommodate all activities of implementing health services at the Puskesmas whose implementation is always evaluated for the success of this modern application. The purpose of this theoretical review is to find out how PMIS is successfully implemented. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are vendor support, IT infrastructure and government regulation and support. It can be concluded that the Puskesmas is one of the first level of health services in an effort to provide health services. This service includes planning, implementing, evaluating, recording, and reporting as outlined in a comprehensive puskesmas management system. With the successful implementation of PMIS it is also necessary to carry out monitoring and evaluation.